Thermodynamic analysis and economic assessment of a carbon dioxide hydrate-based vapor compression refrigeration system using load shifting controls in summer. (1st January 2022) - Hua, Nan; Lu, Tiejun; Yang, Liwei; Mckeown, Andrew; Yu, Zhibin; Xu, Bing; Sciacovelli, Adriano; Ding, Yulong; Li, Yongliang
Highlights: Propose a two-stage carbon dioxide hydrate vapor compression refrigeration system. Cold energy storage is linked with proposed hydrate-based refrigeration system. Thermal-economic analysis of new system using different energy storage strategies. Develop a payback-year map for full storage system in different tariff structures. Abstract: The present work proposed a novel two-stage carbon dioxide hydrate-based vapor-compression refrigeration system. The proposed system applied pure carbon dioxide hydrate as the primary refrigerant and arranged both of hydrate formation and dissociation at the low-pressure stage. The thermodynamic and economic models were developed and then performances of the proposed system using load-levelling storage and full storage operations were evaluated and compared with those of a conventional carbon dioxide single-stage vapor-compression refrigeration system, which is treated as the baseline and with no energy storage. The simulation results indicate that the design capacity of the proposed system using full storage is the largest among the three systems, but with lowest operation cost, and with the incentivization of electricity prices ratio of on and off-peak this cost savings would raise significantly. Noted that the bill structure reveals the load-levelling storage system saves most on the water consumption. Due to the dominant expenditure on the two compressors, compare with the baseline system, the initial capital cost of the full storage system was 75.5% higher, whereas that of the levelling-load storage system was only 21.5% higher. Finally, this paper discussed the economic feasibility on the initial capital cost for the proposed system and developed an indication map to predict the profit years in case of that the new system using load-levelling storage operation replaces the baseline system assuming a system lifetime of 15 years under different electricity prices ratios.